Evaluation of the Sustainability of Urban Market Gardens in the City of Meknes (Morocco) - El Ghazi, Ibrahim; Egah, Janvier; Ahouangninou, Claude; Berni, Imane; Menouni, Aziza; Sadik, Soumia; Amane, Mohammed; Kestemont, Marie-Paule; Jaafari, Samir El (European Scientific Journal, ESJ, 2021)
Market gardening constitutes a basis for food security of urban and peri-urban households. However, market gardening is subject to the use of chemical inputs, selected varieties, and genetically modified organisms. These practices are increasingly controversial and are likely to affect the sustainability of vegetable farms. This study assessed the sustainability of 120 randomly selected market garden farms (Meknes) using the surveys and the market garden production sustainability indicator. The results show that the majority of the farms identified are characterized by low sustainability, with the agroecological dimension being the limiting factor. The improvement of the components "Ecological diversity", "Spatial organization", and "Agricultural practices" are the ways to improve the global sustainability of vegetable production in Meknes. The socio-territorial sustainability of production is characterized by a lack of training for producers, a lack of hygiene and safety in production activities, and a low contribution to employment. The economic dimension is characterized by low viability, low economic transmissibility, and financial autonomy. To perpetuate the market gardening in the city of Meknes, it appears necessary to promote ecological intensification, integrated diversification, and promotion of local inputs to the various types of market gardening farms